"Move backward to make a step forward": Understanding the migration of the highly educated to Sorong City, West Papua, Indonesia. (December 2021) - Malamassam, Meirina Ayumi; Hidayati, Inayah; Setiawan, Bayu; Latifa, Ade
Highly educated people are mainly concentrated in big cities or metropolitan areas. However, some of them choose to move to less developed regions. Using information from in-depth interviews of 15 highly educated migrants that recently moved to Sorong City, a small city in easternmost Indonesia, this study examines the narratives behind their spatial movements. The findings show that promising career development is a critical factor in their migration decision-making process. Although most of them faced difficulties with the limited living amenities in Sorong city, the migrants managed to improve their employability and accelerate their social mobility. However, some migrants expressed their intentions to remigrate from the city in the future. This situation indicates the lack of migrants' social integration and the challenges in the human capital accumulation in the region.